DIFFERENCES IN THE KNEE TORQUE BETWEEN HIGH- AND LOW-BAR BACK SQUAT TECHNIQUES: A PILOT STUDY - Janez Logar; Matej Kleva; Uroš Marušič; Matej Supej; Mitja Gerževič (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2015)
Purpose: The squat is one of the most frequently used exercises in sports training and competitions. There are several squat variations: i) the front squat (FS), ii) the high-bar back squat (HBS) and iii) the low-bar back squat (LBS). As the biomechanics of the LBS technique have been studied to a lesser extent, therefore the purpose of this pilot study was to analyze the differences in knee joint net muscle torque between the HBS and LBS. Methods: One healthy male subject (180.0 cm, 76.0 kg, 26 years) performed 10 steady paced squats (5 HBS and 5 LBS) with additional weight (40.4 kg) to a 90° knee angle. Kinematic and kinetic data were gathered using a high-speed camcorder and a force plate, respectively. The maximal and average knee joint net muscle torques (Mmax and Mavg) were then calculated via 2-dimensional inverse dynamics. Results: A significantly greater Mavg was observed using the HBS technique as compared to the LBS, both during the entire range of the squat (MavgHBS = 221.6 ± 5.1 Nm, MavgLBS= 203.3 ± 10.2 Nm; p = 0.026) as well as during the eccentric (MavgHBS = 226.0 ± 5.9 Nm, MavgLBS= 202.0 ± 14.0 Nm; p = 0.043) and concentric (MavgHBS = 216.2 ± 3.6 Nm, MavgLBS= 205.0 ± 7.9 Nm; p = 0.021) phase separately. Conclusions: It can be concluded that the lower Mavg during the LBS could be due to the load transfer to the hip joint, most likely because of the greater anterior tilt of the torso, which is a direct response to a lower and more posterior bar placement on the back to finally maintain an unchanged centre of mass. Confirmation of these findings in a larger sample would imply that the LBS could be a more appropriate squat technique when knee joint relief is desired.